Automatic Control of the Hybrid Heat Pump for Heating of Multi-Storey Buildings - Sit M.L.; Juravliov A.A.; Timchenko D.V. (Problems of the Regional Energetics)
The work is devoted to control systems for hybrid heat pumps using the heat of return network water and outside air, designed to operate in district heating systems based on CHPP. The aim of the research is to develop control systems for heat pump operating on qualitative, quantitative and quantitative-qualitative heat schedules. The set goal is achieved by introducing two con-trolled heat exchangers: one of "refrigerant-water" type, installed after the evaporator and "re-frigerant-air" type, installed after the gas cooler. The most important results are the hydraulic scheme of the heat pump, the control system scheme of gas superheater installed after the evap-orator and gas supercooler installed after the gas cooler. The significance of the obtained results consists in obtaining a technical solution, which ensures the operation of the heat pump at dif-ferent heating schedules. Equations of heat pump apparatuses have been obtained, in which the influence of flow rate and temperature of the working body on the heat pump operating mode is emphasized. The obtained heat balance equations allowed obtaining structures of automatic con-trol systems for heat exchange apparatuses, compressors and controlling valves of the hybrid heat pump. The developed scheme of the heat pump air duct allowed using a minimum of heat of return network water in the heat pump. It is established that the scheme of this automatic con-trol system should include a functional converter linking the temperature of the outside air and the coordinates of the working body state at the outlet of the gas subcooler.